Direct and correlated responses to bi-directional selection on pre-adult development time in Drosophila montana. (July 2019) - Kauranen, Hannele; Kinnunen, Johanna; Hopkins, David; Hoikkala, Anneli
Graphical abstract: Highlights: Selection was successful towards slow, but not towards fast development. Selection towards fast development led to longer critical day length for diapause. Effects of selection on body weight and cold-tolerance showed no clear trends. Abstract: Selection experiments offer an efficient way to study the evolvability of traits that play an important role in insects' reproduction and/or survival and to trace correlations and trade-offs between them. We have exercised bi-directional selection on Drosophila montana flies' pre-adult development time under constant light and temperature conditions for 10 generations and traced the indirect effects of this selection on females' diapause induction under different day lengths, as well as on the body weight and cold tolerance of both sexes. Overall, selection was successful towards slow, but not towards fast development. However, all fast selection line replicates showed at the end of selection increased variance in females' photoperiodic diapause response and about one hour increase in the critical day (CDL), where more than 50% of emerging females enter diapause. Indirect effects of selection on flies' body weight and cold-tolerance were less clear, as the flies of the slow selection line were significantly heavier and less cold-tolerant than the control line flies after five generations of selection, but lighter and more cold-tolerant at the end of selection. Changes in females' diapause induction resulting from selection for fast development could be due to common metabolic pathways underlying these traits, collaboration of circadian clock and photoperiodic timer and/or by the interaction between the endocrine and circadian systems.